Wheat (Triticum aestivum) response under soil moisture and crop water stress based irrigation scheduling at variable nitrogen regimes - ANKIT,; KHANNA, MANOJ; DASS, ANCHAL; SUDHISHRI, SUSAMA; BABU, SUBHASH; KAUR, RAMANJIT; SHEKHAWAT, KAPILA; PRAJAPATI, VIJAY KUMAR; SAHOO, RABI NARAYAN; SINGH, TEEKAM; MEENA, MAHESH CHAND; UPADHYAY, PRAVIN KUMAR; et al. (The Indian Journal of Agricultural Sciences, 2024)
The field experiment was conducted during winter (rabi) seasons of 2021–22 and 2022–23 at research farm of ICAR-Indian Agricultural Research Institute, New Delhi to examine the water productivity and crop response under soil moisture and crop water stress based irrigation scheduling at variable nitrogen regimes in wheat (Triticum aestivum L.). Experiment was conducted in a split-plot design (SPD) design comprised of 3 irrigation regimes in main plots and 5 graded nitrogen (N) levels in sub-plots, replicated thrice. Irrigation scheduling regimes included I1 (50% available soil moisture depletion-ASMD); I2 (CWSI i.e. crop water stress index based); and I3 (Conventional crop growth stage based). The 5 graded N levels included 0 (N0); 50 (N1); 100 (N2); 150 (N3); and 200 (N4) kg N/ha. Results showed that 50% DASM based irrigation significantly increased grain yield (11.28 and 6.30%), straw yield (5.33 and 5.70%), dry matter accumulation (5.65 and 5.44%), water productivity (11.37 and 6.19%), root length (15.89 and 44.48%), root weight (11.63 and 12.77%) and grain N uptake (20.88 and 14.52%) compared to conventional crop stage based irrigation during 2021–22 and 2022–23, respectively. Among the graded N application, maximum grain yield (4.78 and 4.82 t/ha) and crop water productivity (13.91 and 15.09 kg/ha-mm) were recorded with treatment N4 (200 kg N/ha), but remained statistically at par with N3 (150 kg N/ha) due to the marginal increment beyond 150 kg N/ha. Overall, soil moisture based irrigation at 50% MAD with 150 kg/ha N application proved to be the most effective and economical approach to enhance dry-matter accumulation, yield and water productivity with saving from harmful environmental effects ascending from excessive nitrogen use.